Strategi Pengembangan Kompetensi Penyuluh Di Kota Singkawang (Jurnal Social Economic of Agriculture, 2018)
Reseach purposes to know problems in the development of competence extension agriculture and formulate the right strategy in development of competence in Singkawang. Methode samping used by non probably sampling with convience technic and using SWOT and AHP analisys.Result of SWOT analisys factor internal and external be faced agricultural extension formed strengh opportunity strategy analised to use AHP to determined prominent strategy.Keywords : competence extension, motivation extension, government policy, formal/nonformal education, means of support.